The effect of last meal “Suhoor” timing on diurnal variations in cognitive performance during Ramadan fasting among female athletes - Bougrine, Houda; Ammar, Achraf; Trabelsi, Khaled; Belgacem, Ahlem; Salem, Atef; Chtourou, Hamdi; Jahrami, Haitham; Souissi, Nizar (Frontiers in Nutrition, 2024)
The present study aimed to investigate the effect of the timing of the last meal, "Suhoor", on diurnal variation in cognitive performance during Ramadan intermittent fasting (RIF). In a randomized order, 26 adolescent female athletes (aged 15.9 ± 0.9 y) were tested in three sessions at 7:00 a.m., 12:00 p.m., and 5:00 p.m. across four different conditions: the ten days preceding Ramadan (PR); the final twelve days of Ramadan (RO): two different conditions: Early Suhoor (SEarly), and Late Suhoor (S Late); and, ultimately, the ten days immediately after Ramadan (AR) with an in-between recovery period of ≥24 h. During each test session, the oral temperature (OT), simple reaction time test (SRT), choice reaction time test (CRT), attention test (ATT), and mental rotation test (MRT) were evaluated. The Pittsburgh Sleep Quality Index (PSQI) and daily diary intake were assessed across the three periods. Compared to PR, the sleep parameters assessed by the PSQI were significantly lower during the RO and AR periods. However, neither total dietary intake nor OT showed any changes due to RIF. Compared to PR, the afternoon performances of SRT, CRT, ATT, and MRT significantly declined under both the SEarly and SLate conditions. Notably, midday performance decreased only during S Late, while morning performance remained unaffected in both conditions. Additionally, compared to S Early, these performances were better during S Late in the afternoon and at midday. In summary, nutrient intake timing had a significant effect on the diurnal fluctuations in cognitive functions during Ramadan fasting, particularly around noon and in the afternoon. Our results illustrate the benefits of a late last meal (Suhoor) in preserving optimal morning cognitive abilities and preventing any impairment during the fasted state at midday or in the afternoon, which could affect overall athletic performance.